Pengaruh Theodor NÃ¶ldeke terhadap Studi Sejarah Al-Qur'an di Indonesia - Bariqi, Sirajuddin (Lajnah Pentashihan Mushaf Al-Qur'an, 2018)
Abstract The history of the Qur'an is a new scientific discipline being pioneered by Theodor NÃ¶ldeke. Book of The History of the Qur'an that he wrote has a significant impact on the development of the study of the history of the Qur'an in the muslim world. Previously, muslim scholars put the study of the history of Qur'an into the scope discussion of the Ã¢â‚¬ËœulÃ…Â«mul-Qur'aÂn. Being started from Abu Abd Allah al-ZanjÃ„ÂnÃ„Â« with his work TÃ„ÂrÃ„Â«kh alQur'aÂn (1935), the influence spred to various parts of the world, including Indonesia. This paper will discuss to what extent NÃ¶ldeke's influence is on the works of muslim scholars in Indonesia concerning the history of the Qur'an which is periodically compiled. Starting from the mid-20th century that continues until now, the influence is felt by muslims in Indonesia in the form of works, methodologies used, as well as the responses both positive and negative ones. The birth of works such as that of Abu Bakar Aceh (Sedjarah Al-Qur'an), that of M Quraish Shihab (Sejarah dan Ã¢â‚¬ËœUlum Al-Qur'an), Taufik Adnan Amal (Rekonstruksi Sejarah Al-Qur'an) and A. Athaillah (Sejarah Al-Qur'an: Verifikasi tentang Oentisitas Al-Qur'an) is evidence of that influence. Keywords: History of the Qur'an, Theodor NÃ¶ldeke, Abu Bakar Aceh, M Quraish Shihab, Taufik Adnan Amal, Athaillah.